Profile of Acute Ischemic Stroke Patients Receiving Intravenous Thrombolysis with Recombinant Tissue Plasminogen Activator at Soeradji Tirtonegoro Hospital - Adika Mianoki; Fatikha Fajar Wiati; Hanum Salsabila (Journal of Neurointervention and Stroke, 2025)
Highlight: Most patients showed early neurological improvements after IV thrombolysis The door-to-needle time was  longer than the recommended guidelines A patient profile may guide the optimization of stroke management ABSTRACT Introduction: Acute ischemic stroke is a leading cause of mortality and disability worldwide, including in Indonesia. Intravenous thrombolysis with recombinant tissue plasminogen activator (rtPA) is recommended for eligible patients, but data from Indonesian referral hospitals remain limited. Objective: This study aimed to describe the demographic characteristics, treatment times, and in-hospital clinical measures of patients with acute ischemic stroke receiving intravenous rtPA at Soeradji Tirtonegoro Hospital. Method: A descriptive study analyzed medical records of patients treated with intravenous rtPA between April 2022 and August 2024. Collected variables included age, sex, stroke onset, onset-to-needle time (OTN), vital parameters, comorbidities, door-to-imaging (DTI),  door-to-needle (DTN) times, early ischemic change (EIC), National Institutes of Health Stroke Scale (NIHSS) scores at admission, at 24 hours, and at discharge, Barthel Index at admission and discharge, early neurological improvement (ENI), early neurological deterioration (END), symptomatic intracerebral hemorrhage (sICH), in-hospital mortality, and length of stay (LOS). Result: Most patients were older males (62.2%; median age 62 years). Hypertension was the most common comorbidity, followed by diabetes mellitus and dyslipidemia. The median onset-to-needle time (OTN) was 240 minutes, and 80% achieved a DTI time within 25 minutes. The median DTN time was 80 minutes. Median NIHSS scores improved from 11 on admission to 6 at 24 hours and four at discharge, with ENI in 64.44% and early END in 15.56% of patients. The Barthel Index increased from 3 to 20 during hospitalization. Symptomatic intracerebral hemorrhage occurred in 6,.67%, and in-hospital mortality was 17.78 %. Conclusion: Intravenous rtPA thrombolysis improved neurological and functional measures among acute ischemic stroke patients. However, the prolonged door-to-needle time indicates the need for enhanced in-hospital workflows to accelerate treatment delivery.